Bulgarian Subject Files
The files contain mostly newspaper clippings from western press sources and news agency releases, but there are also brochures on Agriculture, Economic Conditions and Policy, Intellectual life, Population, Prisons and Youth. Of particular interest are files on Human Rights, Minorities, Concentration Camps and Resistance. Accruals not expected